E-goverment dengan Memanfaatkan Teknologi Informasi - Alexsander Yandra (POLITIK, 2016)
AbstrakTransparansi pada proses pengadaan barang dan jasa pada Unit Layanan Pengadaan (ULP) Kota Pekanbaru belum menyentuh kerangka yang substansial. Transparansi pada ULP Kota Pekanbaru secara proses walaupun sudah mengintegrasikan e-goverment dengan memanfaatkan teknologi informasi dan komunikasi (TIK) dalam pengadaan barang dan jasa, yang mempermudah penyedia dalam mengakses paket pengadaan. Tetapi dengan rangkap kerja para personil di ULP berimplikasi terhadap kualitas pengadaan yang dilaksanakan. Preferensi personil yang lebih berorientasi kepada peningkatan pendapatan maka komposisi personil di ULP juga menjadi incaran aparat (pegawai). ULP belum menjadi organisasi yang permanen tetapi masih bersifat ad-hoc. Secara produk pengadaan barang dan jasa ULP masih menjadi lembaga direct yang berfungsi sebagai unit pelayanan dan sekretariat administrasi pengadaan. Pertanggungjawaban produk pengadaan barang dan jasa belum melakukan uji publik sehingga kegiatanya belum terukur. Kata kunci: good local governance, transparansi.Kata kunci: e-government, transparansi, ULP Kota PekanbaruAbstractTransparency of the procurement becomes an important indicator in a good governance. Basically in the process of procurement, the governmen is expected not favoring to specific individuals or groups. Conversely, the procurement of services and goods for public infrastructure still needs the intervention of the elite government to appoint the providers. The transparency in the procurement process of goods and services in Procurement Services Unit (ULP) Pekanbaru city has not touched its substansial framework. Transparency of the procurement process in ULP Pekanbaru recently applies the integrate e-government using of information technology in order to facilitate the providers to access the procurement package. But the double work of the personnel in ULP has implications for the quality of procurement undertaken. Personnel preferences preferably has orientation to increase their income, so the composition of personnel in ULP also to be the target of apparatus (employee). ULP does not become a permanent organization but an ad-hoc. In the process of procurement of goods and services , ULP still has a function as a direct agency that serve as the service unit and its administrative secretariat. The accountability of product procurement has yet to the public test so that its activity is not measurable.Key word: good local governance, trasparency